Avec Mauss et Polanyi, vers une théorie de l'économie plurielle - Laville, Jean-Louis (Revue du MAUSS, 2003)
Mauss and Polanyi sketched the theoretical foundations of a pluralist approach to the economy and began a reflection on social change that was not satisfied with the ritual evocation of a reversal of the system. In other words, instead of an abstract call to an alternative economy, the concrete path of "altereconomies" opens the field of possibilities.
Sociology; Economics
Keywords: altereconomies

Encastrement et nouvelle sociologie économique : de Granovetter à Polanyi et Mauss - Laville, Jean-Louis (Revue Interventions économiques. Papers in Political Economy, 2008)
Le concept d’encastrement s’est imposé dans la nouvelle sociologie économique. Ce texte souligne sa polysémie. Dans une première partie, il rappelle les deux acceptions politique et réticulaire respectivement adoptées par Granovetter et Polanyi. Rapportée à la modernité démocratique, la démarche de Polanyi permet de mettre en évidence un double mouvement caractérisant les rapports entre économie et société, dont les grands traits sont synthétisés dans la deuxième partie. Si l’on adopte une telle lecture, la convergence entre Polanyi et Mauss apparaît alors dans une approche plurielle de l’économie, présentée dans la troisième partie. Selon l’hypothèse esquissée dans la quatrième partie, une telle lecture suggère d’approfondir la teneur des changements institutionnels susceptibles de conforter la pluralité de l’économie, autrement dit de participer à son « ré-encastrement » démocratique. The concept of embeddedness has imposed itself in the New Economic Sociology. This paper highlights the multiple meanings of this term. In a first part, we discuss the political and reticular meanings adopted by Granovetter and Polanyi respectively. In the context of modern democracy, the work of Polanyi shows a double movement characterizing the relations between economy and society, which we develop in the second part. With such a perspective, the convergence between Polanyi and Mauss is highlighted in a plurial approach of the economy, which we discuss in the third part. The hypothesis presented in the fourth part leads us to analyze the content of institutional changes which can confirm the plurality of the economy, and to participate in its democratic « reembeddedness ».
Sociology; Economics
Keywords: GRANOVETTER; Mark; MAUSS; Marcel; 1872-1950; economic sociology; encastrement; niveau d’intégration; sociologie économique